Organizational Performance: Toward Excellent Public Services on State Owned Banks in Indonesia - Sambas Ade Kesuma; Siti Zabedah Saidin; Aidi Ahmi (Romanian Economic Journal, 2017)
The objective of this paper is to discuss the organizational performance. Specifically, this paper discuss the organizational performance in order to improve the public service on the Indonesia state owned bank environment. Over the past five years, the performance of state owned banks shown positive improvement. The performance growth also triggered an increase of its services to the public. The performance of organization is related to how effective organization in moving towards the fulfillment of its objective, mission and how effective the organization in carrying its objective and mission. In general, the objective, vision and mission of state owned banks is always prioritizes public satisfaction as their main customer. While, the mission of state owned banks in general is to consist of providing excellent service to customers by professional human resources and conducting the best banking activities to support the economic improvement of society. Therefore, based on the mission of state owned banks it can be concluded that the improvement of will increasing the achievement of this organization mission, that is excellent financial services to the public by using professional and competence human resources and best facilities.